The Online Student Connectedness Survey: Evidence of Initial Construct Validity - Zimmerman, Tekeisha Denise; Nimon, Kim (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2017)
The Online Student Connectedness Survey (OSCS) was introduced to the academic community in 2012 as an instrument designed to measure feelings of connectedness between students participating in online degree and certification programs. The purpose of this study was to examine data from the instrument for initial evidence of validity and reliability and to establish a nomological network between the OSCS, the Classroom Connectedness Survey (CCS), and the Community of Inquiry Survey (COI), which are similar instruments in the field. Results provided evidence of factor validity and reliability. Additionally, statistically and practically significant correlations were demonstrated between factors contained in the OSCS and established instruments measuring factors related to student connectedness. These results indicate that for the sample used in this study, the OSCS provides data that are valid and reliable for assessing feelings of connection between participants in online courses at institutions of higher learning.